Correlation of minimum inhibitory concentrations between human and animal antimicrobials against Escherichia coli isolated from livestock. (July 2021) - Ozawa, Manao; Kawanishi, Michiko; Uchiyama, Mariko; Mitsuya, Daisuke; Abo, Hitoshi; Koike, Ryoji; Kijima, Mayumi
We analyzed the correlation between minimum inhibitory concentrations (MICs) of antimicrobials used in humans and those used in animals to enable comparison of antimicrobial susceptibility between Escherichia coli isolated from humans and those from animals. We compared the following pairs of MIC data: piperacillin (PIPC) to ampicillin (ABPC), amikacin (AMK) to kanamycin (KM), minocycline (MINO) to oxytetracycline (OTC), and levofloxacin (LVFX) to enrofloxacin (ERFX) using 103 isolates of E. coli from healthy livestock (cattle, pigs, broiler chickens, and layer chickens). Kappa analysis of the agreement for resistance and susceptibility between PIPC and ABPC, AMK and KM, MINO and OTC, and LVFX and ERFX showed almost perfect (κ = 0.81), slight (κ = 0.12), fair (κ = 0.37), and moderate (κ = 0.46) agreement, respectively. Within the antimicrobial pairs, all isolates resistant to the human antimicrobial were also resistant to the veterinary antimicrobial. However, there was less agreement within the pairs for those isolates that were sensitive to the human antimicrobial. The percentage agreement for susceptibility, defined as the percentage of isolates sensitive to both antimicrobials compared with isolates sensitive to both antimicrobials, as well as those sensitive only to the human antimicrobial, was 89.9%, 87.3%, 64.0%, and 89.9% for PIPC and ABPC, AMK and KM, MINO and OTC, and LVFX and ERFX, respectively. Our results suggest that the possibility of missing the resistance for antimicrobials used in human medicine by examining MICs for the equivalent antimicrobials used in veterinary medicine is low.